Accessing Symmetrical Tetraphenyl‐pyrrole‐2‐yl Squaraines Through an Improved Synthesis of 2, 4‐Diphenylpyrrole. Issue 1 (2nd January 2020) - Gut, Arkadiusz; Stosz, Maria; Łapok, Łukasz; Stadnicka, Katarzyna M.; Nowakowska, Maria
Abstract: Synthesis of tetraphenyl‐pyrrole‐2‐yl squaraines is introduced for the first time. An improved, reproducible and straightforward method for the preparation of 2, 4‐diphenylpyrrole‐a key structural synthon for the preparation of the squaraines in question‐is reported. Both, squaraine dyes and all intermediates were fully characterized using spectroscopic methods, viz. 1 H NMR, 13 C NMR, 2D NMR (COSY, HSQC, HMBC), FT‐ATR‐IR, ESI‐HRMS. The structures of tetraphenyl‐pyrrol‐2‐yl squaraines were unambiguously confirmed by single X‐ray analysis. The squaraines studied exhibit an intense absorption bands spanning from ca. 600 to 700 nm, entering to the spectral region, which is highly sought after for biomedical applications and advanced material technologies. Abstract : Symmetrical tetraphenyl‐pyrrole‐2‐yl squaraines: Highly desirable optical properties, viz. absorption in so‐called 'therapeutic window', were induced in squaraine dyes by introducing four phenyl rings into 3, 3′, 5, 5′ positions of the chromophore core.